QANUN: TATA CARA PEMBUATAN QANUN: Catatan Terhadap Praktek Pebuatan Qanun Aceh - Nufiar Nufiar (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
Aceh Qanun an-level regulation Regulation (Regional Regulation) theformulation mechanism should refer to the Act No. 10, 2004. The preparation ofAceh qanun formed on the initiative of the executive or provincial parliament (thePeople's Consultative Council Aceh) were subsequently passed along between theGovernment and the provincial parliament. A rule of law or the regulation levelmust have principles which include: Clarity of purpose, institutional or formingorgans proper, the correspondence between the type and substance, can beimplemented, efficient and effective, formulation clarity and openness. To achievethis purpose the regulation must be made by experts with communityinvolvement. Community involvement is intended as a form of participation of thepublic space in the form of community participation. One form of publicinvolvement is loading qanun draft in the media to accommodate inputs thatreceive input from the community at large.